2006
DOI: 10.1016/j.chembiol.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Production of Fosfomycin and Identification of the Minimal Biosynthetic Gene Cluster

Abstract: Fosfomycin is a clinically utilized, highly effective antibiotic, which is active against methicillin- and vancomycin-resistant pathogens. Here we report the cloning and characterization of a complete fosfomycin biosynthetic cluster from Streptomyces fradiae and heterologous production of fosfomycin in S. lividans. Sequence analysis coupled with gene deletion and disruption revealed that the minimal cluster consists of fom1-4, fomA-D. A LuxR-type activator that was apparently required for heterologous fosfomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
134
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 62 publications
0
134
0
1
Order By: Relevance
“…acute cystitis; FR-900098 and fosmidomycin, antimicrobials undergoing clinical trials for malaria; and phosphinothricin, the active component in several commercial herbicides (Liberty, Basta, and Rely). Second, the methodology needed for gene-based discovery of phosphonate biosynthetic loci has been rigorously established (17)(18)(19)(20)(21)(22)(23). This method relies on the fact that all but two characterized phosphonate biosynthetic pathways begin with the enzyme phosphoenolpyruvate (PEP) mutase (encoded by pepM) (14).…”
Section: Significancementioning
confidence: 99%
“…acute cystitis; FR-900098 and fosmidomycin, antimicrobials undergoing clinical trials for malaria; and phosphinothricin, the active component in several commercial herbicides (Liberty, Basta, and Rely). Second, the methodology needed for gene-based discovery of phosphonate biosynthetic loci has been rigorously established (17)(18)(19)(20)(21)(22)(23). This method relies on the fact that all but two characterized phosphonate biosynthetic pathways begin with the enzyme phosphoenolpyruvate (PEP) mutase (encoded by pepM) (14).…”
Section: Significancementioning
confidence: 99%
“…1). Initially released by a few bacterial species, such as Streptomyces spp [26][27][28] or Pseudomonas syringae, 29 it is now produced synthetically for pharmaceutical purposes. The disodium salt is administered parenterally and the trometamine salt orally.…”
Section: Pharmacokinetics and Pharmacodynamics Descriptionmentioning
confidence: 99%
“…86 In a similar way, Erwinia carotovora produces the carbapenem antibiotics (53). 87 The triggered production of other compounds including fosfomycin (54), 88 geldanamycin (55), 89 pimaricin (56 90 pikromycin (57), 91 rapamycin (6) 92 and stambomycin (58) In a recent study to unlock a cryptic biosynthetic cluster encoding novel naphthalenic octaketide ansamycins, Shen and co-workers firstly investigated the introduction of the strong consitutive promoter ermE* (in a strategy similar to that reported by Bode in 4.2), this resulted in partial activation of the pathway with an increase in the transcriptional levels of only two of the genes. Analysis of the biosynthetic cluster indicated that a putative positive regulator of the LuxR family of transcription factors was encoded, nam1.…”
Section: Quorum Sensing As a Tool For The Regulation Of Secondary Metmentioning
confidence: 99%